Integrated Curriculum Management Based on School Culture as a Strategy for Strengthening Character Education in Integrated Islamic Schools - Syamilah, Izzah; Arifin, Zainal (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyse integrated curriculum management grounded in school culture as a strategy for strengthening character education in Integrated Islamic Schools. The research was conducted at Raudhatul Ulum and Menara Fitrah Integrated Islamic Junior High Schools in Ogan Ilir Regency, involving 18 participants selected purposively based on their roles in curriculum and character education programmes. Participants included of school principals, vice principals for curriculum and student affairs, teachers, guidance and counselling (BK) teachers, and programme coordinators. Demographically, they ranged in age from 30 to 55 years, consisted of both male and female educators, and had professional experience between 5 and 25 years. A descriptive qualitative approach was employed. Data were collected through in depth interviews, observations, and document analysis, and validated using source and method triangulation. Data analysis followed the interactive model of Miles, Huberman, and Saldana. The findings show that school culture based integrated curriculum management is implemented through planning, organizing, implementing, and controlling. Character education is embedded in classroom learning, extracurricular activities, habituation practices, and school culture. The promoted values include religiousness, discipline, social care, independence, and creativity. The study concludes that integrating school culture into curriculum management provides a systematic and sustainable strategy for strengthening character education.